2023
DOI: 10.1111/irv.13150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the risk of hospitalisation among BA.1 and BA.2 COVID‐19 cases treated with sotrovimab in the community in England

Abstract: There are concerns that sotrovimab has reduced efficacy at reducing hospitalisation risk against the BA.2 sub‐lineage of the Omicron SARS‐CoV‐2 variant. We performed a retrospective cohort (n = 8850) study of individuals treated with sotrovimab in the community, with the objective of assessing whether there were any differences in risk of hospitalisation of BA.2 cases compared with BA.1. We estimated that the hazard ratio of hospital admission with a length of stay of 2 days or more was 1.17 for BA.2 compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Our large, population-based study across England contributes to the overall favorable weight of evidence to support the clinical benefit of sotrovimab as an early treatment for COVID-19 through Omicron subvariant predominance periods, especially for patients at higher risk of developing severe symptoms, such as those with severe renal diseases and active cancer. Moreover, our findings also confirm those of a recent study that reported similar proportions of hospital admissions between sequence-confirmed Omicron BA.1 and BA.2 cases treated with sotrovimab [ 25 ]. In addition, our study further extends these findings by also assessing patients treated during periods of Omicron BA.5 prevalence.…”
Section: Discussionsupporting
confidence: 91%
“…Our large, population-based study across England contributes to the overall favorable weight of evidence to support the clinical benefit of sotrovimab as an early treatment for COVID-19 through Omicron subvariant predominance periods, especially for patients at higher risk of developing severe symptoms, such as those with severe renal diseases and active cancer. Moreover, our findings also confirm those of a recent study that reported similar proportions of hospital admissions between sequence-confirmed Omicron BA.1 and BA.2 cases treated with sotrovimab [ 25 ]. In addition, our study further extends these findings by also assessing patients treated during periods of Omicron BA.5 prevalence.…”
Section: Discussionsupporting
confidence: 91%
“…For sotrovimab-treated patients, we also report a reduced risk of hospitalisation or death during BA.1 predominance and non-significant trends for reduced risk during BA.2 and BA.5, possibly not significant due to low event rate and small sample size for this comparison. Harman et al previously reported low proportions of hospitalisations between sequencing-confirmed Omicron BA.1 and BA.2 cases treated with sotrovimab 29. Another retrospective cohort study using Hospital Episode Statistics data in England reported low levels of COVID-19-attributable hospitalisations and deaths in patients presumed to be treated with sotrovimab (based on NHS data showing that 99.98% of COVID-19-mAb-treated individuals received sotrovimab during the study period), with no significant differences in hospitalisation rates during Omicron BA.1, BA.2 or BA.5 predominance 30.…”
Section: Discussionmentioning
confidence: 97%
“…Harman et al previously reported low proportions of hospitalisations between sequencing-confirmed Omicron BA.1 and BA.2 cases treated with sotrovimab. 29 Another retrospective cohort study using Hospital Episode Statistics data in England reported low levels of COVID-19-attributable hospitalisations and deaths in patients presumed to be treated with sotrovimab (based on NHS data showing that 99.98% of COVID-19-mAb-treated individuals received sotrovimab during the study period), with no significant differences in hospitalisation rates during Omicron BA.1, BA.2 or BA.5 predominance. 30 Zheng et al used the OpenSAFELY platform to evaluate the comparative effectiveness of sotrovimab and molnupiravir for preventing severe COVID-19 outcomes from 16 December 2021–10 February 2022.…”
Section: Discussionmentioning
confidence: 99%
“…An English retrospective cohort study of COVID-19 outpatients treated with sotrovimab reported that 133 of 3,230 (4.1%) BA.1 cases and 140 of 3566 (3.9%) BA.2 cases were hospitalized with an adjusted hazard ratio of 1.02 (95% CI: 0.70–1.47) [ 8 ]. Although this study adjusted for age group and vaccination status to account for confounders, additional risk factors such as immunocompromised status were not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…As BA.2 emerged before large-scale discontinuation of sotrovimab in clinical practice, a few observational studies had been able to evaluate BA.2-infected patients who received sotrovimab as treatment [ 8 10 ]. These studies demonstrated no significant differences in hospitalizations in BA.1 versus BA.2-infected patients treated with sotrovimab, although the analyses were either unadjusted for baseline risks or adjusted for age and immunization status only.…”
Section: Introductionmentioning
confidence: 99%